GAMBARAN MANAJEMEN PERAWATAN DIRI PADA PENDERITA HIPERTENSI DI MASA PANDEMI COVID-19 - Felicia Risca Ryandini; Ade Kristianti (Coping: Community of Publishing in Nursing, 2021)
The cases that occurred in Indonesia itself were quite large for the spread of the COVID-19 virus, so the government implemented policies to limit the spread of the COVID-19 virus that conflicted with or intersects with several community interests, one of which was self-care in cases of hypertension. Problems that can arise include: uncontrolled blood pressure, anxiety and fear of going to health services or doing regular health checks that can cause complications in people with hypertension. The aim of this research is describe self care management in hypertension patient on pandemic of COVID-19 era. Design of this research is using cross-sectional approach. Sampling technique used is purposive sampling techniquee used is purposive sampling with total of sample is 62 respondents of hypertension patient. The data is taken by quesionnaire of self care management of hypertension. The result of research shows that the most age is early elder, 46-55 years on 24 respondents (33,9 %), male is 32 respondents (51,6 %), the elementary graduated is 33 respondents (53,2%), married is 53 respondents (88,7 %), farmer is 23 respondents (54,8 %), no smoking patients are 44 respondents (71, 0%), no consumption of alcohol or cafein is 41 respondents (66,1 %), have no complication is 48 respondents (77,4 %), physical activity is 40 respondents (77,4 %) doing physical activity in medium category, diet management is 42 respondents (67,7 %) doing diet in medium category, stress management is 38 respondents (61,3 %) doing enough stress management, using hypertension medicine is 46 respondents (74,2 %) in doing the hypertension medicine medium category. The conclusive of this research is the hypertension patients can increase the self care management well and patient complication occused that be dead reason.